2013
DOI: 10.1371/journal.pone.0081054
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the C242T Polymorphism of the p22-phox Gene (CYBA) on the Interaction between Urinary Sodium Excretion and Blood Pressure in an Urban Brazilian Population

Abstract: BackgroundReactive oxygen species are implicated in the physiopathogenesis of salt-induced hypertension and the C242T polymorphism of the p22-phox gene has been associated with higher superoxide production. This study investigated the impact of this polymorphism on the relationship between urinary sodium excretion (USE) and blood pressure levels in an urban Brazilian population.MethodsWe cross-sectionally evaluated 1,298 subjects from the city of Vitoria-ES, located in the Southeast region of Brazil, by clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In line with these findings, a case-control study of 234 elderly people ( 82 ) reported an interaction between sodium intake and angiotensin-converting enzyme ( ACE ) SNP rs4646994 on the risk of hypertension, where carriers of the “ I/I ” genotype with a high sodium intake (>2 g/day) had an increased risk of hypertension ( P interaction = 0.007). Furthermore, in a cross-sectional study of 1298 healthy adults ( 83 ), those carrying the “ T ” allele of Cytochrome B-245 Alpha Chain ( CYBA ) ( p22phox ) with more than 86.5 mEq sodium per 12 h of urine collection, had increased SBP ( P interaction < 0.001) and DBP ( P interaction = 0.011). Sodium is known to increase BP by reducing vasodilation ( 86 ), while dietary calcium is believed to stabilize intracellular calcium in smooth muscles, thereby reducing vasoconstriction and BP ( 87 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with these findings, a case-control study of 234 elderly people ( 82 ) reported an interaction between sodium intake and angiotensin-converting enzyme ( ACE ) SNP rs4646994 on the risk of hypertension, where carriers of the “ I/I ” genotype with a high sodium intake (>2 g/day) had an increased risk of hypertension ( P interaction = 0.007). Furthermore, in a cross-sectional study of 1298 healthy adults ( 83 ), those carrying the “ T ” allele of Cytochrome B-245 Alpha Chain ( CYBA ) ( p22phox ) with more than 86.5 mEq sodium per 12 h of urine collection, had increased SBP ( P interaction < 0.001) and DBP ( P interaction = 0.011). Sodium is known to increase BP by reducing vasodilation ( 86 ), while dietary calcium is believed to stabilize intracellular calcium in smooth muscles, thereby reducing vasoconstriction and BP ( 87 ).…”
Section: Resultsmentioning
confidence: 99%
“…The interaction between micronutrients and genetic variants on cardiometabolic traits was examined by five Brazilian studies (81)(82)(83)(84)(85). A cross-sectional study of 335 healthy young adults (81), observed a pronounced increase in systolic blood pressure (SBP) (P interaction = 0.016) among carriers of the "G" allele of Angiotensinogen (AGT) SNP rs699 with a higher plasma magnesium (209.3 mg).…”
Section: Interactions Between Micronutrients and Genetic Variants On ...mentioning
confidence: 99%
“…Certain studies have investigated the correlation of the C242T SNP with cardiovascular risk factors, obtaining conflicting results (55)(56)(57). A study involving a South Indian population found a lower frequency of the T allele among individuals with DM2 and coronary disease, compared with a diabetic group without any arterial impairment (58).…”
Section: Discussionmentioning
confidence: 99%
“…The methods for comparing coefficient is either Zou's confidence interval or z-score (Diedenhofen and Musch, 2015 ). In our case, we decided to use z-score, following the approach of other researches (Schreiber et al, 2013 ; Bhattacharjee et al, 2019 ; Younes and Reips, 2019 ).…”
Section: Methodsmentioning
confidence: 99%